Adsorptive removal of arsenic and manganese from groundwater - Addae-Mensah, Afiba (2011)
A thesis submitted to the School of Engineering, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the award of MSc.degree in Water Supply and Environmental Sanitation, 2005